Organizational Performance, Firm Size and Chief Executive Officer’s (CEO’S) Compensation for Firms Listed in Nairobi Securities Exchange, Kenya - Anne, Omamo; obonyo, Peter K’; Muindi, Florence (International Journal of Scientific Research and Management (IJSRM), 2019)
This study examined the link between organizational performance, firm size and CEO’S compensation of firms listed at the NSE. Past studies on the determinants of CEO’S compensation revealed a lack of consensus to the explanation of increases in CEO’S compensation. While most of the studies confirm linkages between organizational performance and CEO’S compensation, they measured organizational performance using financial indicators of performance, the current study investigates the relationship between organizational performance and CEO’S compensation but differs from the previous studies by expanding the measures of organizational performance to include the balanced scorecard measures of financial indicators, customer satisfaction, internal processes and learning and growth elements of performance. Additionally, the study sought to find out the moderating role of firm size on the relationship between organizational performance and CEO’S compensation. The theoretical foundation of this study was based on agency theory. A conceptual model and conceptual hypothesis were drawn from literature and provided directions for this study. The study’s population constituted 60 firms listed at the NSE. Descriptive crossectional survey was adopted for this study. Primary data was collected to capture the opinion of board members on factors that determine levels of CEO’S compensation using semi structured questionnaire. Secondary data was gathered from the financial statements of the listed firms for 2015-2016 financial periods. Descriptive statistics and stepwise regression were used to analyze and interpret the collected data. The study revealed that there was significant and positive relationship between organizational performance and CEO’S compensation. The study further found that firm size had a significant moderating effect on the relationship between organizational performance and CEO’S compensation.